2007
DOI: 10.1177/1049732306298250
|View full text |Cite
|
Sign up to set email alerts
|

Patterns of Knowing as a Foundation for Action-Sensitive Pedagogy

Abstract: Graduate students in the health sciences often juggle full-time careers, demanding programs of study, and family responsibilities. Frustration, a perception of limited caring on the part of role models, and a sense of disengagement, or even despair, are common features of postbaccalaureate study for many of them. Nursing has long recognized the value of multiple perspectives in knowledge development. Previous work involving patterns of knowing not only has advanced the disciplinary knowledge base but has also … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2008
2008
2019
2019

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 34 publications
0
7
0
Order By: Relevance
“…Some have suggested that arts-based interventions help physicians become more empathic and culturally-sensitive, which then leads to better patient health outcomes (e.g., Novack et al, 1997 , pp. 502–509), whereas others have focused on the importance of reflection and imagination for developing insight, emotional understanding of patients, or other valuable “patterns of knowing” (e.g., Berragan, 1998 ; Rodenhauser et al, 2004 ; Averill and Clements, 2007 ).…”
Section: Art Engagement As a Path To Understanding Othersmentioning
confidence: 99%
“…Some have suggested that arts-based interventions help physicians become more empathic and culturally-sensitive, which then leads to better patient health outcomes (e.g., Novack et al, 1997 , pp. 502–509), whereas others have focused on the importance of reflection and imagination for developing insight, emotional understanding of patients, or other valuable “patterns of knowing” (e.g., Berragan, 1998 ; Rodenhauser et al, 2004 ; Averill and Clements, 2007 ).…”
Section: Art Engagement As a Path To Understanding Othersmentioning
confidence: 99%
“…Re-visioning nursing pedagogy in this way, along with cultivating a learning climate that values aesthetic and personal knowing in nursing may help overcome any disinterest in choosing a nursing career in the aged care sector. Averill and Clements (2008) support this recommendation by advocating "the need to reenergize and reorganise the learning experience" (p. 387). A maturing emotional competence within first year nursing students acquired in a safe, non-judgemental environment may improve the student's readiness and preparedness for clinical practice and overcome any potential barriers to learning.…”
Section: Implications For Nursing Practicementioning
confidence: 99%
“…34,35 It is expressed in models and theories and can be integrated into evidence-based practice. Empirical indicators are accessed through the known senses that are subject to direct observation, measurement, and verification.…”
Section: Content Component 3: Patterns Of Knowingmentioning
confidence: 99%
“…34,35 It includes valuing and clarifying situations to create formal moral and ethical behaviors intersecting with legally prescribed duties. It emphasizes respect for the person, the family, and the community that encourages connectedness and relationships that enhance attentiveness, responsiveness, communication, and moral action.…”
Section: Content Component 3: Patterns Of Knowingmentioning
confidence: 99%
See 1 more Smart Citation